Evaluating the GASING Method Training on Teachers’ Mathematical Competence and Intrinsic Motivation in Papua: A Self-Determination Theory Perspective - Mai Rosalli Matondang; M Solehuddin; Arie Rakhmat Riyadi; Idat Muqodas; Yohanes Surya (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to examine the effectiveness of an intensive GASING method (Gampang, Asyik, dan Menyenangkan: Easy, Fun, and Enjoyable) training program in enhancing mathematical competence and intrinsic motivation among elementary school teachers in Papua, analyzed through the lens of Self-Determination Theory (SDT). A pre-experimental one-group pretest–posttest design, supplemented by qualitative analysis, was employed. Thirty-one teachers in Jayapura completed a 17-day (more than 130 hours) intensive program at Cenderawasih University. The study used a 100-point mathematical competence test (validated by the Surya Institute) and trainers’ daily journals as research instruments. Quantitative data were analyzed using descriptive statistics, N-gain scores (Hake, 1999), and Cohen’s d effect size, while qualitative data from journals were analyzed thematically within the framework of Self-Determination Theory (SDT) to explore changes in participants’ psychological motivation. The results demonstrated a substantial increase in mathematical competence, with a mean gain of 55.58 points (from 38.52 to 94.10; +144.3%), an N-gain score of g = 0.904 (high category), and a large effect size (Cohen’s d = 3.41). All five mathematical components and all four instructional groups consistently achieved high N-gain scores (g = 0.854–0.936). The qualitative findings indicate that the program’s effectiveness was grounded in the systematic fulfillment of the three core psychological needs of SDT: competence (through structured mastery progression), autonomy (through opportunities for creative agency), and relatedness (through the formation of a collective identity as “Smart Papua”). Gamification elements, music, chants, and structured practice reduced anxiety while fostering sustained intrinsic motivation. These findings contribute to the extension of Self-Determination Theory in collectivist cultural contexts and offer practical implications for transformative teacher professional development in Eastern Indonesia.